Using digital technologies to support Self‐Directed Learning for preservice teacher education. Issue 1 (1st March 2013) - Bullock, Shawn Michael
Abstract : This article begins with the perspective that teacher education programmes are cultural institutions and are thus compelled to respond to the societal push for teachers to be conversant in so‐called twenty‐first‐century skills, grounded primarily in the ability to use digital technologies for pedagogical purposes. The results of an attempt to provide teacher candidates with an opportunity to engage in a sustained self‐directed learning experience using digital technologies are presented. Findings indicate that candidates selected tasks for themselves for both personal and pragmatic reasons, and that external pressures played a significant role in candidates' ability to see their tasks through to satisfactory completion. The focus on self‐directed learning provided me with an opportunity to address some pragmatic concerns raised by the perceived need to teach technology skills in a teacher education course while, more importantly, providing an atypical learning experience that encouraged teacher candidates to engage in metacognitive talk about their experiences learning with and through technology. The article concludes by suggesting that self‐directed learning experiences are worthwhile in teacher education, although experiences framed explicitly around digital technologies may tacitly reinforce a positive bias toward using technology for teaching.